Anti-Inflammatory Effects of Artemisia Leaf Extract in Mice with Contact Dermatitis In Vitro and In Vivo - Chanyong Yun; Youngchul Jung; Wonjoo Chun; Beodeul Yang; Junghyun Ryu; Chiyeon Lim; Jung-Hoon Kim; Hyungwoo Kim; Su-In Cho (Mediators of Inflammation)
The leaves of Artemisia argyi Lev. et Vant. and A. princeps Pamp. are well known medicinal herbs used to treat patients in China, Japan, and Korea with skin problems such as eczema and itching, as well as abdominal pain and dysmenorrhoea. We investigated the anti-inflammatory effects of Artemisia leaf extract (ALE) using CD mice and Raw 264.7 cells. The effects of ALE on histopathological changes and cytokine production in ear tissues were assessed in mice with CD induced by 1-fluoro-2,4-dinitrobenzene (DNFB). Moreover, the anti-inflammatory effects on production levels of prostaglandin E2 (PGE2) and nitric oxide (NO) and expression levels of cyclooxygenase 2 (COX-2) and inducible nitric oxide synthase (iNOS) were investigated in Raw 264.7 cells. Topical application of ALE effectively prevented ear swelling induced by repeated DNFB application. ALE prevented epidermal hyperplasia and infiltration of immune cells and lowered the production of interferon- (IFN-) gamma (γ), tumour necrosis factor- (TNF-) alpha (α), and interleukin- (IL-) 6 in inflamed tissues. In addition, ALE inhibited expression of COX-2 and iNOS and production of NO and PGE2 in Raw 264.7 cells. These results indicate that Artemisia leaf can be used as a therapeutic agent for inflammatory skin diseases and that its anti-inflammatory effects are closely related to the inhibition of inflammatory mediator release from macrophages and inflammatory cytokine production in inflamed tissues.